Spine and spinal cord injury in children - Indira Jayakumar; N Saravana Pandian; Priyavardhini Venkatachalapathy; Srinivasan Paramasivam (Wolters Kluwer Medknow Publications, 2017)
Trauma to the spine can cause injuries involving spinal cord, vertebra or both. Although less frequent compared to adults, Traumatic Spinal Cord Injury (TSCI) in the pediatric population is not rare and has high morbidity and mortality with significant physiological and psychological consequences. Pediatric patients with TSCI have different mechanisms of injury but better neurological recovery potential when compared to adults. TSCI should be strongly suspected in the presence of neck pain, abnormal neurological exam, high-risk mechanism ofinjury or a distracting injury, even in the absence ofradiological abnormality A high index of suspicion should be maintained in trauma victims until a spinal injury is identified or ruled out. As in Traumatic Brain Injury (TBI), hypoxia and hypotension can worsen secondary injury to the spinal cord and adversely affect neurologic outcome.